Transformasi Literasi Akademik di Era Digital: Peran Mendeley dalam Meningkatkan Kualitas Penulisan Ilmiah dan Integritas Akademik Mahasiswa - Destrin; Maria Nuansa; Purwandaron; Muhammad Khoirib (PT. Giovani Publisher, 2026)
Digital transformation has significantly changed academic literacy practices in higher education, particularly in reference management and scientific writing. However, many students still face difficulties in citing sources, compiling bibliographies, and understanding the principles of academic integrity. This Community Service Program (PKM) aimed to improve the quality of scientific writing and strengthen students’ academic integrity through the utilization of **Mendeley** as a reference management tool. The program was conducted for students of the Master of Social Studies Education Program at Universitas Bhinneka PGRI Tulungagung using socialization, training, technology implementation, mentoring, and evaluation methods. The materials covered digital academic literacy, Mendeley installation and operation, reference management, automatic citation, bibliography generation, and plagiarism prevention. The results indicated a significant improvement in participants’ competencies in reference management and scientific writing. The average participant score increased from 58.7 in the pre-test to 87.3 in the post-test. Furthermore, most participants were able to operate Mendeley independently and correctly apply automatic citations in their academic papers. The program had a positive impact on improving the efficiency of scientific writing, the quality of academic work, and students’ understanding of academic integrity. Therefore, the use of Mendeley has proven effective as a supporting tool for academic literacy transformation in the digital era and has the potential to sustainably enhance students’ scientific publication productivity.